2022
DOI: 10.1017/s0021932022000050
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in child and mother’s characteristics influencing the use of insecticide treated net in Nigeria

Abstract: Nigeria accounts for a quarter of malaria cases worldwide, which can be prevented with the use of insecticide treated nets (ITN). While studies have documented mother-related characteristics influencing use of ITN, regional variations in the influence of those factors are not well known. This study investigated nine factors (age, place of residence, education, religion, wealth, number of children in the household, sex of child, age of child and previous experience of child mortality) as possible predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
2
2
1
Order By: Relevance
“…This study has shown that there are differences in weight abnormalities between the north and south and variations among ethnic groups. Unlike earlier studies Alabi & Ramsden, 2022) that suggest that the south may have better health and social indicators than the south, this study, like that of Adejoh et al (2023), found the reverse. Women in the north have healthier weight than their counterparts in the south.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This study has shown that there are differences in weight abnormalities between the north and south and variations among ethnic groups. Unlike earlier studies Alabi & Ramsden, 2022) that suggest that the south may have better health and social indicators than the south, this study, like that of Adejoh et al (2023), found the reverse. Women in the north have healthier weight than their counterparts in the south.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding that the two regions have notable differences in abnormal weights is in tandem with the reports of earlier studies that investigate north-south differences in Nigeria (Adejoh et al, 2023;Alabi, 2023;Alabi & Ramsden, 2022). Specifically, the finding that the north has a higher prevalence of underweight than the south may suggest that southern women have a healthier weight than the northern women.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, the findings on IPV experience contradicts the tenets of theory. Like earlier studies (Alabi et al, 2020;Alabi & Badru, 2021;Adejoh et al, 2022), this study has contributed to CSCFH and argued that being 'conservative' does not necessarily attract failure neither does being 'cosmopolitan' lead to success in all social and health outcomes. The association between IPV experience and IPV acceptance is not clear, and future studies, in this regard, should be careful about making causal inferences.…”
Section: Discussionsupporting
confidence: 54%
“…However, recent studies conducted on the use of insecticide-treated nets [ITNs] (Adejoh et al, 2022), and obesity/overweight (Alabi & Badru, 2021) do not give credence to the assumption of CSCFH that the south exhibits better health and social behaviours than the north. This is so because a higher proportion of residents in the north utilized ITNs and have lower risks of overweight/obesity than their counterparts in the south.…”
Section: The Rationale For Investigating a North-south Dichotomymentioning
confidence: 99%